2007
DOI: 10.1590/s0100-54052007000100016
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade de fungicidas cúpricos e sistêmicos sobre o fungo Cladosporium cladosporioides em cafeeiro

Abstract: No controle integrado de doenças reside a preocupação com a seletividade dos produtos utilizados, visando associar o sucesso no controle das doenças à preservação de agentes antagonistas de fungos deletérios à qualidade do café além dos aspectos de segurança ambiental e do trabalhador.No cafeeiro, o controle da ferrugem e da cercosporiose coincide com o período de colonização de Cladosporium sp. sobre os frutos desta cultura. Há uma sucessão enorme de fungos que se associam aos frutos do cafeeiro nos seus dife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Throughout the research developed to verify the role of microorganisms in the quality, it was observed that, contrary to the other ones, the genus Cladosporium was associated to good quality beverages (Chalfoun et al, 2007). This relation, confirmed by other researches and later observations, raised interest for its usage as an antagonist agent against fungi deleterious to quality of the coffee (Figure 2 A B C Ciênc.…”
Section: Fungus Associated To Coffee Grains and Fruitsmentioning
confidence: 83%
See 2 more Smart Citations
“…Throughout the research developed to verify the role of microorganisms in the quality, it was observed that, contrary to the other ones, the genus Cladosporium was associated to good quality beverages (Chalfoun et al, 2007). This relation, confirmed by other researches and later observations, raised interest for its usage as an antagonist agent against fungi deleterious to quality of the coffee (Figure 2 A B C Ciênc.…”
Section: Fungus Associated To Coffee Grains and Fruitsmentioning
confidence: 83%
“…de Vries. The main distinctive characteristics that allowed the identification of the species (Figure 3), were the prominent conidial scars, conidiophores without nodules, conidia without septa or only a common septum, and ellipsoidal or lemon-shaped format (Chalfoun et al, 2007).…”
Section: Fungus Associated To Coffee Grains and Fruitsmentioning
confidence: 99%
See 1 more Smart Citation
“…As médias da incidência do gênero Cladosporium foram de 69,921,4 e de 81,314,2% para as secagens com e sem inversão do sentido do fluxo de ar, respectivamente. Research, Society and Development, v. 9, n. 7, e34973197, 2020 (CC BY O gênero Cladosporium é correlatado na literatura à cafés de melhor qualidade (Chalfoun et al, 2007). Foi identificado por outros autores que cafés classificados como bebida mole possuem maior incidência deste gênero, comparado à bebidas de qualidade inferior (Alves 1996).…”
Section: Análise Microbiológicaunclassified
“…Thus, both the fl owering plant species and the honeydew secreted by aphids may have infl uenced the bee attraction for the fungus sources. Another factor that may have infl uenced the occurrence and collection of Cladosporium over this period was the presence of coffee plantations near the apiary during fruit ripening, because of the commonness of the coffee berry contamination by fungi (Chalfoun et al 2007).…”
Section: May -June 2009mentioning
confidence: 99%